Imaging sequence for joint myocardial T1 mapping and fat/water separation. Issue 1 (29th July 2018) - Nezafat, Maryam; Nakamori, Shiro; Basha, Tamer A.; Fahmy, Ahmed S.; Hauser, Thomas; Botnar, René M.
Abstract : Purpose: To develop and evaluate an imaging sequence to simultaneously quantify the epicardial fat volume and myocardial T1 relaxation time. Methods: We introduced a novel simultaneous myocardial T1 mapping and fat/water separation sequence (joint T1 ‐fat/water separation). Dixon reconstruction is performed on a dual‐echo data set to generate water/fat images. T1 maps are computed using the water images, whereas the epicardial fat volume is calculated from the fat images. A phantom experiment using vials with different T1 /T2 values and a bottle of oil was performed. Additional phantom experiment using vials of mixed fat/water was performed to show the potential of this sequence to mitigate the effect of intravoxel fat on estimated T1 maps. In vivo evaluation was performed in 17 subjects. Epicardial fat volume, native myocardial T1 measurements and precision were compared among slice‐interleaved T1 mapping, Dixon, and the proposed sequence. Results: In the first phantom, the proposed sequence separated oil from water vials and there were no differences in T1 of the fat‐free vials ( P  = .1). In the second phantom, the T1 error decreased from 22%, 36%, 57%, and 73% to 8%, 9%, 16%, and 26%, respectively. In vivo there was no difference between myocardial T1 values (1067 ± 17 ms versus 1077 ± 24 ms, P  = .6). The epicardial fat volume was similar for both sequences (54.3 ± 33 cm 3 versus 52.4 ± 32 cm 3, P  = .8). Conclusion: The proposed sequence provides simultaneous quantification of native myocardial T1 and epicardial fat volume. This will eliminate the need for an additional sequence in the cardiac imaging protocol if both measurements are clinically indicated.